A Comparison of The Effectiveness of Hollow Prism and Parallel Plans The Measurement of Fludia's Refresh Index: Case Study On Aquades and Alcohol - Rizqi Fajar Shidiq; Indira Gustaviana Nugroho; Irfan Daniel; Fuji Hernawati Kusumah; Rabina Amara Yusra; Ahmad Suryadi (Jurnal Multidisiplin Indonesia, 2023)
A refractometer is a tool used to measure the refractive index of fluids. However, there are several issues, including the considerable cost involved and the fact that not all school laboratories have this tool. Therefore, we conducted a study to compare the accuracy of refractive index values using a hollow prism and a plan parallel prism. Among the various methods available today, refraction is a relatively simple and cost-effective method for determining the refractive index of fluids. In measuring the refractive index of fluids, the use of containers or vessels is essential. Following a review of existing studies, two commonly used types of vessels were identified: the cube-shaped vessel (plan parallel) and the hollow prism. This research aims to compare the refractive index results obtained using a hollow prism and a plan parallel prism, using two samples—namely, distilled water (aquades) and alcohol—which have predetermined values in the refractive index table. The results indicate that the refractive index value for aquades using a plan parallel prism is 0.97, while with a hollow prism, it is 1.33, where the true refractive index value is 1.33. For alcohol, the results using a plan parallel prism are 0.91, and with a hollow prism, it is 1.35, where the true refractive index value is 1.36. The conclusion drawn is that using a hollow prism yields refractive index values for both aquades and alcohol that closely approximate the true refractive index, compared to the use of a plan parallel prism.